Sebuah Penundaan Pemasangan Stent pada Beban Trombosis Tinggi - Kurniawan, Catur Rizky; Widito, Sasmojo (Jurnal Klinik dan Riset Kesehatan, 2025)
Deferred stenting is a revascularization strategy that involves two stages of implementation, where stent placement is delayed for a predetermined period after stable coronary blood flow is achieved. This approach aims to reduce the risk of complications such as slow-flow or no-reflow phenomena, particularly in patients with high thrombus burden (HTB). This study seeks to explore the benefits and limitations of deferred stenting in HTB cases, as well as its impact on long-term clinical outcomes. The primary benefits of deferred stenting include significant reduction in thrombus burden, improved myocardial perfusion quality, and decreased risk of complications such as distal embolization and slow-flow phenomena. Research indicates that this technique can enhance left ventricular ejection fraction (LVEF) and reduce infarct size. However, deferred stenting also carries potential complications, including the risk of re-occlusion, need for unplanned revascularization, and increased bleeding risk due to prolonged use of parenteral anticoagulants. Evaluation of various studies reveals inconsistent results regarding the effectiveness of deferred stenting. Some studies report significant benefits in reducing thrombus burden and improving clinical outcomes, while others highlight a higher risk of complications without meaningful short-term improvements. The CRUSADE score is used to assess bleeding risk in HTB patients, with scores >20 indicating a high bleeding risk and contraindicating the use of GPIIb/IIIa inhibitors. Overall, deferred stenting offers potential benefits in HTB cases, its implementation should be carefully considered due to associated risks and additional costs. Further research is needed to determine the optimal protocols and assess the long-term benefits of this technique.